2017
DOI: 10.1177/1077546317706886
|View full text |Cite
|
Sign up to set email alerts
|

Stability and perturbation analysis of a one-degree-of-freedom doubly clamped microresonator with delayed velocity feedback control

Abstract: In this paper, a study on a doubly clamped microresonator actuated by two symmetrical electrodes is carried out to investigate its dynamic properties with delayed velocity feedback control. A stability chart of the linearized system depicting delay time versus feedback gain is drawn first, which is actually nonperiodic. Moreover, stability switches do exist in this system. Then, the method of multiple scales is used to determine the existence, stability and dynamic properties of small amplitude vibration in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 48 publications
2
6
0
Order By: Relevance
“…Perturbation methods are applied to obtain the modulation equations that govern the amplitude and phase response of the resonator. Examples of these studies can be found in microbeams [107,166,217,[261][262][263][264][265][266][267][268][269][270][271][272][273][274][275][276][277][278][279], torsional mirrors [280,281], self-excited resonators [282][283][284][285], PZT based MEMS models [286][287][288], MEMS filters [171], MEMS arch resonators [169,289], carbon Nanotubes [290], and coupled oscillators [291]. The influence of secondary-resonance excitations on MEMS has been also studied.…”
Section: Nonlinear Response Of Mems Resonators Using Perturbation Methodsmentioning
confidence: 99%
“…Perturbation methods are applied to obtain the modulation equations that govern the amplitude and phase response of the resonator. Examples of these studies can be found in microbeams [107,166,217,[261][262][263][264][265][266][267][268][269][270][271][272][273][274][275][276][277][278][279], torsional mirrors [280,281], self-excited resonators [282][283][284][285], PZT based MEMS models [286][287][288], MEMS filters [171], MEMS arch resonators [169,289], carbon Nanotubes [290], and coupled oscillators [291]. The influence of secondary-resonance excitations on MEMS has been also studied.…”
Section: Nonlinear Response Of Mems Resonators Using Perturbation Methodsmentioning
confidence: 99%
“…They found that positive feedback control gain can strengthen system stability, whereas negative feedback can lead to an unstable response gain. Moreover, Han et al (2018) extended this study to large delay times and showed the appearance of a stability switches.…”
Section: Introductionmentioning
confidence: 82%
“…Thus, some researchers have been interested to analyze the effect of parameters of delayed feedback controllers on the system performances. The authors Shao et al (2013) and Han et al (2018) analyzed the effects of delayed velocity feedback control on an electrostatic microactuator actuated by one electrode and by two symmetrical electrodes. They found that positive feedback control gain can strengthen system stability, whereas negative feedback can lead to an unstable response gain.…”
Section: Introductionmentioning
confidence: 99%
“…It is of great significance to study the multistability and necessary conditions for inducing it either for avoiding this phenomenon or making use of it. Thus, multistability of vibrating systems of micro resonators has been studied experimentally and numerically during these decades [16]. Via experiments, Mohammadreza investigated the dynamic response of an electrostatic micro-actuator in the vicinity of the primary resonance and the parametric one [17].…”
Section: Introductionmentioning
confidence: 99%